PENGGUNAAN AGILE PROGRAMMING DALAM PENGEMBANGAN PERANGKAT LUNAK - Firmansyah, Ricky (Jurnal Informatika Kaputama (JIK), 2026)
Agile Programming is a leading approach in modern software development because it offers flexibility and rapid adaptation to changing user needs. It emphasizes team collaboration, short iterations, and continuous product delivery, making it relevant in today’s dynamic digital era. However, its implementation still faces challenges, including organizational resistance, limited understanding of Agile principles, and difficulties shifting from traditional methods. This study explores the effectiveness of Agile Programming, analyzes organizational challenges, and identifies strategies to overcome them through a systematic literature review. It examines Agile frameworks such as Scrum, Kanban, and Extreme Programming, including their use in Indonesia and globally. Findings show that Agile can improve software quality and efficiency, but success depends on intensive training, senior management support, and deep cultural change within organizations.